Statistical evaluation and analysis of road extraction methodologies using a unique dataset from remote sensing - Cardim, Guilherme Pina [UNESP]; da Silva, Erivaldo Antônio [UNESP]; Dias, Mauricio Araújo [UNESP]; Bravo, Ignácio; Gardel, Alfredo (MDPI, 2018)
In the scientific literature, multiple studies address the application of road extraction methodologies to a particular cartographic dataset. However, it is difficult for any study to perform a more reliable comparison among road extraction methodologies when their results come from different cartographic datasets. Therefore, aiming to enable a more reliable comparison among different road extraction methodologies from the scientific literature, this study proposed a statistical evaluation and analysis of road extraction methodologies using a common image dataset. To achieve this goal, we setup a dataset containing remote sensing images of three different road types, highways, cities network and rural paths, and a group of images from the ISPRS (International Society for Photogrammetry and Remote Sensing) dataset. Furthermore, three road extraction methodologies were selected from the literature, in accordance with their availability, to be processed and evaluated using well-known statistical metrics. The achieved results are encouraging and indicate that the proposed statistical evaluation and analysis can allow researchers to evaluate and compare road extraction methodologies using this common dataset extracting similar characteristics to obtain a more reliable comparison among them.
Keywords: Evaluation metrics; Image dataset; Methodologies review; Remote sensing images; Road network extraction